2018
DOI: 10.1038/s41366-018-0082-5
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate targets FTO and inhibits adipogenesis in an mRNA m6A-YTHDF2-dependent manner

Abstract: Our findings provide mechanistic insights into how mA is involved in the EGCG regulation of adipogenesis and shed light on its anti-obesity effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 34 publications
0
72
0
Order By: Relevance
“…Wang et al (44) reported that m 6 A modification affects the translation of patatin like phospholipase domain containing 2 (PNPLA2) and uncoupling protein 2 (UCP2) to regulate adipogenesis. Wu et al (53,54) reported that fat mass and obesity-associated gene (FTO) and YTHDF2 cooperatively mediate cyclin A2 (CCNA2) and cyclin dependent kinase 2 (CDK2) expression through m 6 A methylation, further influencing cell cycle progression and adipogenesis. METTL3, as a methyltransferase, catalyzes the formation of m 6 A and plays important roles in various biologic processes (23,55).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (44) reported that m 6 A modification affects the translation of patatin like phospholipase domain containing 2 (PNPLA2) and uncoupling protein 2 (UCP2) to regulate adipogenesis. Wu et al (53,54) reported that fat mass and obesity-associated gene (FTO) and YTHDF2 cooperatively mediate cyclin A2 (CCNA2) and cyclin dependent kinase 2 (CDK2) expression through m 6 A methylation, further influencing cell cycle progression and adipogenesis. METTL3, as a methyltransferase, catalyzes the formation of m 6 A and plays important roles in various biologic processes (23,55).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several promising agents may have potentials to treat MDs by targeting m 6 A, such as m 6 A inhibitors. It is known that FTO negatively regulated m 6 A levels and positively regulated adipogenesis, thus we can use FTO inhibitors (rhein, radicicol, epigallocatechin gallate, entacapone and meclofenamic acid) [91,136,[138][139][140] to remove the potential effect of FTO. In addition, ALKBH5 is positively related to the frequent immune reactions [123], if we rule out the effects of ALKBH5 on immune cells via using ALKBH5 inhibitor (IOX3) [141], the immune-related MDs will be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Suppressing adipogenesis by promoting cell cycle transition in mitotic clonal expansion [89] YTHDF2 Inhibiting autophagy and adipogenesis by decreasing protein expression of ATG5 and ATG7 and shortening the lifespan of their m 6 A-modified mRNAs [87] Suppressing adipogenesis by increasing m 6 A methylation of CCNA2 and CDK2 and reversing the methylation effect of FTO on CCNA2 and CDK2 [90,91] Inhibiting adipogenesis via the downregulation of CCND1 [92] NAFLD FTO Down-regulating mitochondrial content and up-regulating TG deposition [101] Promoting hepatic fat accumulation by increasing the expression of lipogenic genes, including FASN, SCD and MOGAT1, and intracellular TG level in HepG2 cells [101] Increasing oxidative stress and lipid deposition [99] YTHDF2 Increasing lipid accumulation by decreasing both PPARα mRNA lifetime and expression [105] METTL3 Increasing lipid accumulation by decreasing both PPARα mRNA lifetime and expression [105] Hypertension m 6 A-SNPs EncodIing β1-adrenoreceptor, a hypertension-susceptibility candidate gene [108,109] Altering BP-related gene expression, mRNA stability and homeostasis [110] Cardiovascular diseases FTO Decreasing fibrosis and enhancing angiogenesis in mouse models of myocardial infarction [111] METTL3 Driving cardiomyocyte hypertrophy by catalyzing methylation of m 6 A on certain subsets of mRNAs [112] Decreasing eccentric cardiomyocyte remodeling and dysfunction [112] Inhibiting cellular autophagic flux and promoting apoptosis in hypoxia/reoxygenation-treated cardiomyocytes [113] Osteoporosis METTL3 Inhibiting adipogenesis and adipogenic differentiation via JAK1/STAT5/C/EBPβ pathway in bone marrow stem cells [119] Inhibiting osteoporosis pathological phenotypes, consisting of decreased bone mass and increased marrow adiposity via PTH/PTH1R signaling axis [118] FTO Promoting the differentiation of adipocyte and osteoblast by upregulating GDF11-FTO-PPARγ signalling way [116] Enhancing the stability of mRNA of proteins which function to protect osteoblasts from genotoxic damage through Hspa1a-NF-κB signaling way [120] Immune-related MDs ALKBH5 Expressing highly in organs enriched in immune cells with frequent immune reactions [10,123] METTL3 Stimulating T cell activation and the development of T lymphocytes in the thymus by regulating the translation of CD40, CD80 and TLR4 signaling adaptor TIRAP transcripts in den...…”
Section: Mettl14mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, epigallocatechin gallate (EGCG), a catechin in green tea, plays an anti-adipogenesis role. EGCG could increase not only the m 6 A modification of CCNA2 and CDK2 but also the expression of YTHDF2 [106]. And YTHDF2-mediated decay reduced the expression of CCNA2 and CDK2 mRNAs, thereby impairing adipogenesis.…”
Section: The Role Of M 6 A-binding Proteins In Adipogenesismentioning
confidence: 96%